Joden en moslims onder vuur: Over antisemitisme en islamofobie in hedendaags Nederland - Vellenga, Sipco (Religie & Samenleving, 2015)
In recent years, the Netherlands has been challenged frequently with public incidents of anti-Semitism and Islamophobia. After discussing the complex concepts of anti-Semitism and Islamophobia, presenting the theoretical approach to these phenomena and describing the societal context in which they are embedded, this article analyses the developments of the numbers of reported expressions of anti-Semitism and Islamophobia in the Netherlands since the turn of century. It relates these developments to outburst of violence in the Middle East and to acts of violence committed in the name of Islam in the West, and to various experiences of threat in the context of Dutch multi-ethnic society, changes in national identity and globalization.